Description of Appendicitis Patients Post-Appendectomy at Prof. Dr. H. Aloei Saboe Hospital Gorontalo in 2023 - Aryaputra, fadhil; Abdul, Romy; Antu, Yuniarty; Siregar, Muchtar Nora Ismail; Kasim, Vivien Novarina A (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Appendicitis is an acute or chronic inflammation of the appendix caused by obstruction of the lumen. According to the World Health Organization (WHO), appendicitis ranked eighth as a global cause of death in 2014. Objective: To describe the characteristics of post-appendectomy appendicitis patients at Aloei Saboe Hospital, Gorontalo, in 2023. Methods: A retrospective descriptive study was conducted in June–August 2024 at Aloei Saboe Hospital, Gorontalo. The population included appendicitis patients who underwent appendectomy between January–December 2023. Using purposive sampling, 98 patient medical records were analyzed. Data were described based on gender, age, and surgical procedure. Results: Most patients were female (64.3%). The highest age distribution was late adolescence (17–25 years) at 39.8%. The most frequent surgical technique performed was open appendectomy (53.1%), followed by other procedures. Conclusion: At Aloei Saboe Hospital, the majority of post-appendectomy appendicitis patients were female, predominantly in late adolescence, with open appendectomy being the most common surgical method. These findings are expected to provide useful information and education for individuals with high-risk factors for appendicitis.